2023
DOI: 10.3389/fcimb.2023.1260068
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome dysbiosis in men who have sex with men increases HIV infection risk through immunity homeostasis alteration

Kangjie Li,
Jielian Deng,
Cong Zhang
et al.

Abstract: ObjectivesRecent studies pointed out that gut microbiome dysbiosis in HIV infection was possibly confounded in men who have sex with men (MSM), but there is a lack of evidence. It also remained unclear how MSM-associated gut microbiome dysbiosis affected human health. This study aimed to compare the differences in gut microbiome changes between HIV and MSM and reveal the potential impacts of MSM-associated gut microbiome dysbiosis on the immune system.MethodsWe searched available studies based on the PubMed da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…Gay men, due to their tendency to engage in unprotected receptive anal intercourse, may exhibit a unique composition of human faecal microbiota, as previously reported. 42 Consistent with prior research, 42 our analysis revealed altered abundances of Bacteroides, Prevotella, and Clostridium in the feces of those MSM patients on ART. Since this study lacked an MSM control group without HIV infection, we were unable to ascertain whether the increase in faecal Prevotellaceae abundance observed in the INRs was due to MSM behaviour or a direct effect of HIV infection.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Gay men, due to their tendency to engage in unprotected receptive anal intercourse, may exhibit a unique composition of human faecal microbiota, as previously reported. 42 Consistent with prior research, 42 our analysis revealed altered abundances of Bacteroides, Prevotella, and Clostridium in the feces of those MSM patients on ART. Since this study lacked an MSM control group without HIV infection, we were unable to ascertain whether the increase in faecal Prevotellaceae abundance observed in the INRs was due to MSM behaviour or a direct effect of HIV infection.…”
Section: Discussionsupporting
confidence: 89%
“…4 Prevotella is also associated with inflammation, opportunistic infections, and autoimmune diseases. 42 In another study, the abundance of Bacteroides was significantly reduced in both IRs and INRs, and this reduction may potentially be linked to systemic immune activation and chronic inflammation in vivo. 34 Collectively, the decrease in gut IGKC + IgA + plasma cell levels in INRs may further diminish IgA production and delay the restoration of the gut mucosal barrier, thereby promoting host immune overactivation and microbial translocation.…”
Section: Discussionmentioning
confidence: 92%